Large-scale transient simulation for consequence analysis of hydrogen-doped natural gas leakage and explosion accidents - Tong, Sirui (2023)
Transporting blended hydrogen natural gas through existing natural gas pipeline networks is an important strategy for meeting the growing demand for hydrogen energy. However, gas leakage poses a serious safety concern. This study conducts a large-scale simulation of gas leakage and explosion accidents in a hydrogen-doped natural gas station and aims to evaluate the impact of pipeline pressure and leakage direction on the accident consequences. Simulation results indicated that the high pipeline pressure led to more accumulated flammable gas, which caused severer explosion disasters. Within the 100s simulation period, the cumulative volume of the flammable gas cloud reached 2329.80 m3 under 4 MPa pipeline pressure, and the peak explosion overpressure increased by 69.64% compared with the 1 MPa case. Leakage directions also significantly affect the evolution of accidents. Suppose the leakage direction is towards living areas, flammable gas is more likely to accumulate in confined spaces up to 2363.20 m3. The gas explosion will severely damage the building structure with a 17 kPa explosion overpressure and 7 kPa shock wave intensity. Interaction with wind and the disturbance of obstacles also contributed to the flammable gas cloud accumulation, which increased peak values of explosive overpressure.